English for Architectural conservation: An ethnographic investigation into the language features of a new undergraduate programme. - Babbitt, Ian (2015)
Although ESP and EAP researchers have sought to understand the language features of many different disciplines in the academy, emerging disciplines offer opportunities for vibrant new research. Exploring such disciplines in a second-language environment offers an even richer opportunity to not just identify, but also create content to help non-native English speaking students understand the linguistic elements of their discipline. This dissertation is an ethnographic investigation into the language features of a newly established undergraduate architectural conservation programme based in an English-medium Hong Kong university. The research questions sought to identify key language features, vocabulary and genres of the architectural conservation discipline and ways to address them pedagogically. Specifically, in this dissertation, I identify conservation oriented values-based analysis, the statement of significance genre and discipline-specific vocabulary as key features of the discipline and created three activities that address them respectively. For answering the research questions, I was inspired by ethnographic methodologies like “thick participation” (Sarangi, 2006) and prolonged engagement with the participants (Flowerdew, 2013). Applying ethnography as methodology (Lillis, 2008), this dissertation seeks to present an emic perspective of a faculty developing a unique undergraduate curriculum and the student body moving through it. The research design promoted high levels of joint-participation between the researcher and participants at every stage of the process: planning, needs analysis, content creation, testing and reflection. While applying source and method triangulation to verify lacks, wants and needs, through the research design I isolate some of the present-situation issues of this student body and the target-situation requirements for success in the conservation field from the faculty. This led to the creation of the particular activities fashioned specifically for undergraduate conservation students in a second-language environment. As such, this research is either the beginning stages of a new in-the-discipline English course, or, as argued in the conclusion, a potential framework for a robust integrated content-and-language approach. Importantly, this architectural conservation programme is in a distinctive circumstance. It is the only English-language undergraduate conservation programme in the region and one of a very few undergraduate programmes world-wide. As Asian economies continue to develop and architectural and heritage conservation increases in prominence due to expanding urbanisation, it is critical to begin to understand the language features of this culturally potent academic and professional discipline. This dissertation is a first but necessary step that will hopefully lead to further research.